Exploring the universe of the elderly who depend on family caregivers - Moraes, Gerídice Lorna Andrade de; Silva, Maria Josefina da (Rev Rene, 2004)
This is an exploratory study that aims at identifying the family caregivers’ role and relationship with the elderly, listing care given to the elderly and the caregivers’ daily activities. Data were collected through structured interviews with 20 caregivers who were randomly chosen among 72 others. Data were organized according to interview topics and their accounts were included as illustrations for analysis. The results showed that most caregivers are women who are eight companions or daughters of the dependent elderly. For them, there are difficulties in their tasks, such as: physical effort, tiredness, discouragement and stress. Nevertheless, they also feel satisfied for returning all the care once given to them by their parents.